KARAKTER PROTEIN ICP11 PADA DNA UDANG VANNAMEI (Penaeus vannamei) YANG TERINFEKSI White Spot Syndrome Virus (WSS V) - Yuni Kilawati; Win Darmanto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
The aim of this study was to support policy of government to lessen import and improve export of non migas presented characteristic of genetic of white prawn mains (Penaeus vannamei) so that this product can be yielded in Indonesia with high quality which do not fail with import product. Special goals wishing to be reached at this research is to analyze the genetic characteristic DNA with Polymorphism Chain Reaction (PCR) and primer ICP11. The background of this research was difference among vannamei prawn DNA characteristic that have infected by viruses. With experimental methods ten healthy post larva of white prawn cultured in aquarium and invected by WSSV virus in 1ml/10 l marine water dossage with three time replication during 7 days in culture. To know these infection, the sample were analyze with specific primer ICP11.